SIFAT PENGGERGAJIAN DAN PEMESINAN ENAM JENIS KAYU HTI - Jamal Balfas; Osly Rachman Rachman (Pusat Penelitian dan Pengembangan Hasil Hutan, 1989)
This paper presented the result of study on sawing and machining properties of six Indonesian wood species being developed as raw materials for the wood working industries. The sawing properties studied comprise of sawn timber recovery, sawing velocity and power consumption. Whereas the machining properties of the timber were tested according to the modified ASTM D-1666 as described in the Forest Products Research Institute Report No. 160 (1982).The result showed that all of the species has good sawn timber recovery, i.e. more than 50%. Three of them can be cut eastiy wilh higher sawing velocity and lower power consumption in comparison with the other three. The species that have good or very good machining properties is merkuyung (Shorea johorensis). Species of meranti merah (Shorea fallax) has relatively poor machining properties. Whereas the other four species are good in some properties and fair to poor in others.